THE EFFECT OF BRAIN-BASED LEARNING ON STUDENTS' CONCEPT MASTERY AND MOTIVATION IN LEARNING ELECTRIC CIRCUIT - Aulianuriry Sani, - (2018)
Teaching approaches in some school are still concentrating on memorizing. Teachers have to make the learning meaningful for the students. One of the alternative tool is by using Brain-Based Learning. The purpose of this research is to investigate the effect of Brain-Based Learning on students' concept mastery and motivation in learning electric circuit for 8th grade students. The method used in this research was experimental research. The research design that used is pretest and posttest design. The sample was taken by cluster random sampling technique. Participants were 49 students at one of International Junior High School in Bandung, Indonesia. Students of experiment group learnt with Brain-Based Learning (N=26) while students in control group learnt with lectured-based learning (N=23). The results of students' concept mastery that learnt using Brain-Based Learning is better than students' concept mastery that learnt using lectured-based learning. The improvement of students' concept mastery can be noticed by independent t-test with significant 0.003. Based on the analysis of N-Gain of students' concept mastery results, there are 3.84% students got high improvement, 73.07 % students got medium improvement, 11.53% students got low improvement, and 3.84% students are stable. While in control group 52.38% students got medium improvement, 38.09% students got low improvement, 4.76% students are stable, and 14.28% students are decreasing. Then, the results of students' motivation that learned using Brain-Based Learning is better than students' motivation that learnt using lectured-based learning. The improvement of students' motivation could be noticed by Mann-Whitney test with significant 0.014. Furthermore, this research shows there is positive correlation between students' concept mastery and motivation on experiment group. Based on this results showed that Brain-Based Learning can be an alternative tool to improve students' concept mastery and students' motivation significantly. Pendekatan mengajar di beberapa sekolah masih berkonsentrasi pada mengingat. Guru harus membuat pembelajaran yang bermakna bagi siswa. Salah satu alternatif pendekatan mengajar adalah dengan menggunakan Brain-Based Learning. Tujuan penelitian ini adalah untuk mengetahui pengaruh Brain-Based Learning terhadap penguasaan konsep dan motivasi siswa dalam pembelajaran rangkaian listrik untuk siswa kelas 8. Metode yang digunakan dalam penelitian ini adalah penelitian eksperimental. Desain penelitian yang digunakan adalah desain pretest dan posttest. Sampel diambil dengan teknik cluster random sampling. Peserta adalah 49 siswa di salah satu SMP Internasional di Bandung, Indonesia. Kelompok eksperimen belajar dengan Brain-Based Learning (N=26) sementara kelompok kontrol belajar dengan pembelajaran berbasis ceramah (N=23). Hasil penguasaan konsep siswa yang belajar menggunakan Brain-Based Learning lebih baik daripada siswa yang belajar menggunakan pembelajaran berbasis ceramah. Peningkatan penguasaan konsep siswa pada topik rangkaian listrik dapat dilihat dengan independent t-test dengan signifikansi 0.003. Berdasarkan hasil analisis hasil penguasaan konsep siswa, terdapat 3.84% siswa mengalami peningkatan tinggi, 73.07% siswa mengalami peningkatan sedang, 11.53% siswa mengalami peningkatan rendah, dan 3.84% siswa stabil. Sedangkan pada kelompok kontrol 52.38% siswa mengalami peningkatan sedang, 38.09% siswa mengalami peningkatan rendah, 4.76% siswa stabil, 14.28% siswa mengalami penurunan.. Kemudian, hasil motivasi siswa yang belajar menggunakan Brain-Based Learning lebih baik daripada motivasi siswa yang belajar menggunakan pembelajaran berbasis ceramah. Peningkatan motivasi siswa dapat diketahui melalui Mann-Whitney test dengan signifikansi 0.014. Selanjutnya, penelitian ini menunjukkan ada korelasi positif antara penguasaan konsep dan motivasi siswa pada kelompok eksperimen.. Berdasarkan hasil ini menunjukkan bahwa Brain-Based Learning dapat menjadi salah satua alternatif untuk meningkatkan penguasaan konsep siswa dan motivasi siswa secara signifikan.